The Influence of Aluminum Thickness on Energy Absorption and Stability of Circular Crash Box Performance Under Axial Load - Diah Wulandari; Harus Laksana Guntur; Sigit Tri Wicaksono; Willy Artha Wirawan (Universitas Muhammadiyah Magelang, 2025)
The need for improved vehicle safety, particularly in the face of rising road traffic accidents, makes the optimization of crash box designs crucial. This study addresses the impact performance of circular cross-section crash boxes, focusing on how variations in aluminum thickness affect energy absorption and deformation behavior under axial impact loading. A combination of numerical simulations and experimental tests was used to evaluate the crash box performance across different aluminum thicknesses ranging from 1 mm to 3 mm. The results show that increasing thickness improves energy absorption, with the 3 mm thick specimen absorbing the highest energy of 7.3089 kJ, while the 1 mm specimen absorbed only 1.1018 kJ. However, thicker specimens exhibited higher peak forces and force fluctuations, suggesting potential instability after the peak load, while intermediate thicknesses 1.5 mm and 2 mm provided a better balance of energy absorption and structural stability. This research contributes to the development of more efficient crash box designs by providing insights into the optimal material thickness for crashworthiness, with a recommended thickness range of 1.5 mm to 2 mm.